Learner-Centered Pedagogy and Preaching: A Postmodern Framework for Transformation of Preacher and Listener - Moore, Bethany Joy (2024)
This essay will contribute to the ongoing conversation related to postmodern homiletics by engaging with the elements of learner-centered teaching. Recognizing that modernist methods have diminished effectiveness for the postmodern hearer, learner-centered preaching holds potential value by realigning preaching with the cultural shift in theological beliefs about authority, power, and community. Learner-centered teaching, represented by Maryellen Weimer, is a pedagogical approach rooted in democratic and egalitarian values that focuses on these changes in the classroom: the role of the teacher, the balance of power, the function of content, the responsibility for learning, and the method of evaluation. This essay will present the advent of learner-centered teaching and outline its elements. Next, the relationship between teaching and preaching will be examined. Then, an exploration of the context of learner-centered preaching. After that, each learner-centered teaching element will be considered focusing on how they have been utilized in preaching and offering proposals of how they could be integrated. Finally, conclusions will be drawn about the power of learner-centered preaching for the transformation of speaker and hearer. The end goal of learner-centered preaching is a change in Christian practice; therefore, more than just discussing the theory of learner-centered preaching, this essay will provide praxis for immediate implementation.
Keywords: learner-centered preaching; preaching pedagogy; learner-centered; theological practice; homiletical theology; Postmodernism; Homiletics; Preaching